SEM-PLS Training at Universitas Islam Negeri Maulana Malik Ibrahim - Bambang Widjanarko Otok; Cindy Cahyaning Astuti; Angga Dwi Mulyanto; Purhadi Purhadi; Shofi Andari; Achmad Choiruddin; Santi Wulan Purnami (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
At Universitas Islam Negeri Maulana Malik Ibrahim Malang in 2024 SEM-PLS training will develop data analysis capabilities for lecturers and students to enhance their work on quality scientific publications. The Department of Mathematics at Faculty of Science and Technology conducted the session on May 21, 2024, where 40 people participated. Training and mentoring stands as the service method which features instruction about SEM-PLS theory alongside practical utilization of SmartPLS software for implementation. Observation activities together with documentation assessment and satisfaction questionnaire responses determine the program's outcome. Participant satisfaction reached an exceptional level because they showed positive feedback about the material presented. Time constraints together with a constrained space area negatively affected this event. This training achieved success in providing extensive SEM-PLS understanding to students and lecturers. The activity builds campus research capacity. The organization of similar consecutive training courses is highly suggested because it will boost academic knowledge in data analysis fields.